Evaluasi Kapasitas Seismik Gedung Beton Bertulang dengan Metode Pushover Analysis - Darmansyah, Ghina Pricillia; Maidiawati, Maidiawati; Honesti, Leli (Universitas Andalas, 2024)
The Surgical Building and Central Sterile Supply Department of Solok City Regional Hospital is a reinforced concrete building which was just completed in January 2024. In this research, the seismic capacity of the surgical building and CSSD of Solok City Regional Hospital will be evaluated with and without wall contributions using non-linear static analysis methods with software. SeismoStruct. The capacity curve in the comparison between wall and wall models has a significant difference, where the lateral strength with walls in the X direction increases by 6.3% and in the Y direction by 15.83%, the stiffness in the model with walls is also greater than the model without walls where the wall stiffness in the X direction increased by 32.88% and in the Y direction by 73.75%, and ductility also increased in the X direction by 105.43% and in the Y direction by 145.28%. Based on the results of structural performance based on FEMA 356, the level of structural performance without the influence of walls in the X and Y directions and with the influence of walls in the X and Y directions is obtained, namely Immediate Occupancy (IO). Based on the results of this analysis, the evaluation that having a full brick wall can increase the seismic capacity in terms of lateral strength, lateral stiffness and ductility of the Surgery Building and Central Sterile Supply Department of Solok City Regional Hospital.